Response of canopy structure, light interception and grain yield to plant density in maize. (10th September 2018) - Li, J.; Xie, R. Z.; Wang, K. R.; Hou, P.; Ming, B.; Zhang, G. Q.; Liu, G. Z.; Wu, M.; Yang, Z. S.; Li, S. K.
Abstract: Good canopy structure is essential for optimal maize ( Zea mays L.) production. However, creating appropriate maize canopy structure can be difficult, because the characteristics of individual plants are altered by changes in plant age, density and interactions with neighbouring plants. The objective of the current study was to find a reliable method for building good maize canopy structure by analysing changes in canopy structure, light distribution and grain yield (GY). A modern maize cultivar (ZhengDan958) was planted at 12 densities ranging from 1.5 to 18 plants/m 2 at two field locations in Xinjiang, China. At the silking stage (R1), plant and ear height increased with plant density as well as leaf area index (LAI), whereas leaf area per plant decreased logarithmically. The fraction of light intercepted by the plant ( F ) increased with increasing plant density, but the light extinction coefficient ( K ) decreased linearly from 0.61 to 0.39. Taking the optimum value of F (95%) as an example, and using measured values of K for each plant density at R1 and the equation from Beer's law, the corresponding (theoretical) LAI for each plant density was calculated and optimum plant density (9.72 plants/m 2 ) obtained by calculating the difference between theoretical LAIs and actual observations. Further analysis showed that plant density ranging from 10.64 to 11.55 plants/m 2 yielded a stable GY range. Therefore, taking into account the persistence time for maximum LAI, the plant density required to obtain an ideal GY maize canopy structure should be increased by 10–18% from 9.72 plants/m 2 .